2021
DOI: 10.3389/fmars.2021.583188
|View full text |Cite|
|
Sign up to set email alerts
|

In situ Pumping Rate of 20 Marine Demosponges Is a Function of Osculum Area

Abstract: Sponges play a key role in the transfer of energy and nutrients into many benthic ecosystems, and the volume of water they process is an important regulator of these fluxes. Theoretical scaling relationships between sponge volume, osculum cross-sectional area, and pumping rates were recently proposed and confirmed for small sponge specimens in the lab. To examine how these relationships apply to field populations we measured, in situ, the pumping rate (PR) of 20 species representative of different morphologies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(44 citation statements)
references
References 74 publications
2
32
0
Order By: Relevance
“…However, the successive decrease in pumping rate (after 2 days) and the gradual production of a membrane to close the oscula remain unclear but could represent a trade‐off between increasing ventilation and keeping the energetic coast of pumping reasonable. In S. australiensis , body expansion is correlated with an increase in osculum area, and osculum area is the main determinant of pumping rate in this and many other species (Goldstein et al, 2019; Morganti et al, 2021). Perhaps the increase in pumping rate only represents a physiological consequence of the body expansion and is then quickly brought back to normal, decreasing the osculum size by producing an oscular membrane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the successive decrease in pumping rate (after 2 days) and the gradual production of a membrane to close the oscula remain unclear but could represent a trade‐off between increasing ventilation and keeping the energetic coast of pumping reasonable. In S. australiensis , body expansion is correlated with an increase in osculum area, and osculum area is the main determinant of pumping rate in this and many other species (Goldstein et al, 2019; Morganti et al, 2021). Perhaps the increase in pumping rate only represents a physiological consequence of the body expansion and is then quickly brought back to normal, decreasing the osculum size by producing an oscular membrane.…”
Section: Discussionmentioning
confidence: 99%
“…In sponges, pumping rate is correlated with OSA (e.g. Goldstein et al, 2019; Morganti et al, 2021). In the case of S. australiensis , this relationship was calculated on 20 sponges (following Yahel et al, 2005) and was found as PR = 6.55 OSA 1.43 (Figure S6).…”
Section: Methodsmentioning
confidence: 99%
“…Suggesting a constant density of pumping units (choanocytes) throughout any given sponge size, and assuming simple geometric (isometric) scaling V~OSA 3/2 , [17] suggested a theoretical scaling of Q~OSA 3/2 , which has been experimentally supported and confirmed in other studies, see Table 4 in [15]. However, [6,7] found in recent in situ studies on 20 demosponges that Q on average increased allometrically Q = a 1 OSA b1 with scaling exponent b 1 ≈ 0.75, 1.07 and 0.67 (instead of the theoretical value of b 1 = 3/2), thus suggesting that the choanocyte density may not be constant but on the contrary decreases with sponge size.…”
Section: Introductionmentioning
confidence: 62%
“…Data on sponge size and pumping rates (filtration rates) are important for ecological studies in determining the grazing impact, matter transport and nutrient cycling of observed populations of sponges [2][3][4][5][6]. While sponge volume (V) may be more difficult to measure or estimate in situ than the osculum cross-sectional area (OSA), the latter has also been used as a correlation parameter [7], who used the following allometric relationships to characterize sponges:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation